Balancing sales needs with supply chain needs: production control as the arbiter. (2015) - Ozawa, Hiroshi; Liker, Jeffrey K.
The bullwhip effect is a problem of variation in customer demand that gets increasingly large as it propagates backward through the supply chain. A common assumption is that the company must learn to better respond to demand changes through better information systems leading to elaborate scheduling algorithms and 'visibility' of demand in real-time. The Toyota production system starts with the foundation of a levelled schedule and seeks to reduce the problem itself by smoothing demand, thus reducing variability in schedules, and at the same time reducing the lead time of response. This paper, for the first time, explains in detail how Toyota levels the schedule and still manages to satisfy customer demand. It requires cooperation between sales and production mediated by production control. Information displays are very simple using nothing more complicated then spreadsheets.